PREDICTING MORTALITY OUTCOME IN NEONATES DIAGNOSED WITH HYPOXIC ISCHEMIC ENCEPHALOPATHY: A CROSS-SECTIONAL STUDY. - Saumya Singh; Manisha Kumari; Bhupendra Narain (Student's Journal of Health Research Africa, 2023)
Objectives